Enhancing Student Religiosity Through Islamic Content and Influencer Expertise: Social Media Contribution as Mediator - Khotimah, Khusnul; Hakim, Abdul; Robiansyah, Robiansyah; Sandy, Aisyah Trees (Faculty of Education and Teacher Training of UINSI Samarinda, 2025)
The rise of social media has altered how young Muslims learn about their faith, but the effect on their everyday religious practices is unclear. To comprehend how Islamic content and influencers impact religious practices, this study makes use of the Social Learning Theory and the Uses and Gratifications Theory. It also examines social media contribution as a potential link in the chain. 180 Muslim students from 13 faculties at the University of Mulawarman were given a structured questionnaire as part of a quantitative study. Purposive sampling was used to choose respondents, considering the population's infinite size and two particular requirements: frequent interaction with Muslim influencers and Islamic content on social media and active use of social media. Data were gathered using adapted instruments from earlier research, and PLS-SEM was used for analysis. The findings demonstrate that the quality of Islamic content significantly influences religiosity practices both directly and indirectly (through social media contribution). The practice of religiosity is not directly impacted by Muslim influencer expertise, but it does have a notable indirect impact through social media contributions. These results emphasize how crucial interactive engagement and high-quality Islamic teachings are in promoting religious behavior. These findings highlight the importance of high-quality Islamic teachings and interactive engagement in encouraging religious behavior. The study offers helpful insights for Islamic education by highlighting the need for relatable, reliable content and influencers who can promote value-driven engagement. It enables us to comprehend how youth religiosity is shaped by digital spaces and how structured online interaction can reinforce it.